Synaptic and cellular profile of neurons in the lateral habenula. - Frank Julius Meye; Salvatore eLecca; Kristina eValentinova; Manuel eMameli (Frontiers in Human Neuroscience, 2013)
The lateral habenula (LHb) is emerging as a crucial structure capable of conveying rewarding and aversive information. Recent evidence indicates that a rapid increase in the activity of LHb neurons drives negative states and avoidance. Furthermore, the hyperexcitability of neurons in the lateral habenula, especially those projecting to the midbrain, may represent an important cellular correlate for neuropsychiatric disorders like depression and drug addiction. Despite the recent insights regarding the implications of the LHb in the context of reward and aversion, the exact nature of the synaptic and cellular players regulating LHb neuronal functions remains largely unknown. Here we focus on the synaptic and cellular physiology of LHb neurons. First, we discuss the properties of excitatory transmission and the implications of glutamate receptors for long-term synaptic plasticity; second, we review the features of GABAergic transmission onto LHb neurons; and finally, we describe the contribution that neuromodulators such as dopamine and serotonin may have for LHb neuronal physiology. We relate these findings to the role that the LHb can play in processing aversive and rewarding stimuli, both in health and disease states.